Do Co‐Worker Conflicts Enhance Daily Worries about Job Insecurity: A Diary Study. Issue 1 (30th July 2018) - Garrido Vásquez, Mauricio E.; Kälin, Wolfgang; Otto, Kathleen; Sadlowski, Janne; Kottwitz, Maria U.
Abstract : The long‐term negative consequences of job insecurity on employees' health and well‐being have been demonstrated by several studies, but there is very little evidence on the daily experience of job insecurity and on the factors that may influence it. Therefore, we investigated whether short‐term changes occur in the experience of job insecurity and whether these are influenced by daily co‐worker conflicts. We carried out a diary study, in which 66 employees answered a questionnaire over the course of five working days. We conducted a multilevel analysis in which we included co‐worker conflicts as a predictor, and type of contract, emotional stability, and aggregated job insecurity perceptions as control variables. Our results revealed that job insecurity varies on a daily level, and that 23 per cent of the variance could be explained at a within‐person level. Co‐worker conflicts were a significant positive predictor for perceived job insecurity in subsequent days after controlling for aggregated job insecurity perceptions at person level. Reversed causation was not found. Practical implications for organisations should focus on the promotion of positive social relations in the work environment in order to mitigate or avoid the negative consequences of social stressors in uncertain times.